PENGARUH UKURAN PERUSAHAAN, EARNING PER SHARE DAN KOMITE AUDIT TERHADAP AUDIT DELAY: Studi Empiris pada Perusahaan Jasa Sub Sektor Property dan Real Estate Yang Terdaftar di Bursa Efek Indonesia pada Tahun 2016 – 2020 - Muhammad Chalid Saputra; Hari Stiawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to analyze the effect of firm size, earnings per share (EPS) and audit committee on the length of audit delay. Firm size is measured using the natural log of total assets, earnings per share is measured by looking at the total earnings per share on the income statement, the audit committee is measured by looking at the number of audit committee members presented in the corporate governance section of the annual report, and audit delay is measured by calculate the amount of days difference from the closing date of the company's books to the date of issuance of the independent auditor's report. This type of research is descriptive research with a quantitative approach. Determination of the sample in this study was carried out using a purposive sampling method on 35 property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2016 – 2020. The sample data was obtained as much as 175 data, then outliers were carried out as many as 6 companies, so that the final sample data on This study contains 145 data. The results of this study conclude that (1) firm size has a positive effect on audit delay, (2) earnings per share (EPS) has a negative effect on audit delay, while (3) the audit committee has no effect on audit delay. Meanwhile, simultaneously, (4) firm size, earnings per share (EPS) and audit committee have an effect on audit delay.